Land use and groundwater quality: The case of Baixo Acaraú Irrigated Perimeter, Brazil - Andrade, Eunice; Lopes, Fernando; Palácio, Helba; Aquino, Deodato; Alexandre, Deborah (Revista Ciência Agronômica, 2010)
The aim of this work was to identify and to investigate the determining factors of water table quality in the Irrigated Perimeter of Baixo Acaraú, Ceará, Brazil, using factor analysis/principal component analysis (FA/PCA). It was sampled nine shallow wells spread out on two different types of land: uncultivated area (A1) and irrigated area (A2). Groundwater was sampled monthly from Dec/2003 to Nov/2005, Nov/2006, Mar and April/2007. We measured the following parameters: pH, electrical conductivity (EC), and concentrations of Na+, Ca2+, Mg2+, K+, Cl-, PO4-, NH4-, NO3-, SO4-2, HCO3- and CO3- 2. The PCA resulted in a model composed of three components that explained 93.06% and 83.72% of the total variance of the data set from A1 and A2, respectively. It was found that the determining factors of water quality were the mineralization processes and anthropogenic activities in both areas. The anthropogenic activities in the irrigated area were related to nitrogenous fertilizers, while those in the uncultivated area were associated with the presence of septic tanks (from the lack of sewage treatment).